In Situ Measurement of Concrete Static Modulus of Elasticity: Proof of Concept Implementation. Issue 3 (4th July 2021) - Mante, David M.; Coleman, Zachary W.; Romano, Christopher; Simmonds, Tony
ABSTRACT: This paper reports a laboratory implementation of a prototype sensor for the measurement of in situ concrete static modulus of elasticity. Sensor measurements for a trial concrete mixture were generated, post-processed, and calibrated to best match companion ASTM C469 modulus of elasticity testing performed on the same mixture for concrete ages up to 28 days. The sensor prototype measurements demonstrated close agreement with ASTM C469 testing with approximately 90% of calibrated sensor prototype measurements within ±5% of companion testing. The initial sensor prototype implementation reported in this study affirms the feasibility of in situ concrete modulus of elasticity measurement and justifies further sensor development and implementation efforts.